La familia y el aprendizaje en niños del nivel inicial 2 de la Escuela Dr. Luis Felipe Zapater cantón Loja. Período 2023-2024 - Jiménez Arboleda, Angely Lisbeth (2024)
From the moment they decide to make a home, both men and women are aware that they must transmit teaching-learning to their children, actively participating in the educational process, in their values, principles and decisions, hence, their positive involvement takes part in a favorable form in the academic performance and comprehensive development of the child, proving that the family is the cornerstone of their self-development and daily training. In this study, the active and collaborative participation of families and learning in children of the initial level 2 of the Dr. Luis Felipe Zapater school, from the city of Loja, during the academic period 2023-2024. For this research a qualitative methodology was used, with a non-experimental and inductive design and of a documentary nature, applying an interview and observation sheet to parents, teachers and students. As a result, it was obtained that families participate actively in different educational and cultural activities inside and outside of school, besides parents have shown to assume responsibilities by promoting their integration in their children's learning. Additionally, it was evident that the family is so important in the socio-emotional and academic development of children, since as the teacher mentioned in the interview "the family plays an active role in the education of their children" since home, for this reason, here the establishment of routines and habits that contribute to the general well-being of the infants is encouraged, which later will be reflected in the classroom and in their daily life at that moment and in the future. In conclusion, it was determined that, indeed, the family maintains its active participation in the learning of the boys and girls at level 2 during the 2023-2024 academic periods. Key words: the family, learning-teaching, Luis Felipe Zapater School, initial level 2.